Building an Inclusive Climate for Intercultural Dialogue: A Participant‐Generated Framework. (22nd April 2019) - Broome, Benjamin J.; Derk, Ian; Razzante, Robert J.; Steiner, Elena; Taylor, Jameien; Zamora, Aaron
Abstract: This study investigates the question of how to build an inclusive environment for intercultural dialogue. Using the university campus as a context for our research, we conducted a facilitated idea generation workshop in which participants identified a set of dialogic competencies, followed by individual interviews in which we explored participants' perceptions of the relationships among these competencies. Interviews were conducted utilizing a software‐assisted, idea‐structuring methodology referred to as Interpretive Structural Modeling (ISM). Based on our results, we constructed a framework that depicts the overall flow of influence among the set of dialogic competencies identified by the participants. While findings confirm the importance placed in current literature on factors such as listening and empathy, they provide a more sophisticated and nuanced perspective on how to accomplish one of the oft‐stated goals of intercultural dialogue, which is to help participants examine their unconscious biases, prejudices, and privileges.